Preparation of ethyl cellulose bimodal nanofibrous membrane by green electrospinning based on molecular weight regulation for high-performance air filtration - Wang, Qibin; Shao, Zungui; Sui, Jian; Shen, Ruimin; Chen, Ruixin; Gui, Zeqian; Qi, Yude; Song, Wenzhengyi; Li, Guoxin; Liu, Yifang; Zheng, Gaofeng (International journal of biological macromolecules, 2024)
Preparing bio-based air filtration membrane through green electrospinning strategy is a vital approach to alleviating environmental and energy crises. However, the development of related biomaterials and method for regulating membrane structure are still lacking. In this study, ethyl cellulose (EC) bimodal nanofibrous membrane was prepared by electrospinning using ethanol and water as solvents to achieve high-performance air filtration. A new strategy for bimodal fiber molding based on molecular weight modulation was proposed. The EC polymer chains with medium molecular weights were subject to the highest degree of inhomogeneity of solvent intrusion, and there were significant differences in viscous forces “microscopically”, leading to the formation of bimodal structure by inhomogeneous stretching of the jet. The well-defined bimodal structure endowed EC membrane with excellent air filtration performance. The filtration efficiency for PM0.3, pressure drop, quality factor were 99.11 %, 42.2 Pa, and 0.112 Pa−1, respectively. Compared to the commonly used zein, EC cost just 12.77 %, and its solution had a 50 % longer shelf life, making it a more desirable biomaterial. This work will facilitate the application of more biomaterials in air filtration, promote the green fabrication of high-performance air filtration membranes, and realize sustainable development. [Display omitted] •The solvent intrusion control strategy was proposed.•Polymer molecular weight and solvent ratio were regulated to form bimodal fibers.•High-performance air filer made of only ethyl cellulose by green electrospinning.•Ethyl cellulose was first discovered to achieve green electrospinning.